Lithofacies and depositional environment of the Siwalik Group in Samari-Sukaura River area, Central Nepal - Syangbo, Dev Kumar; Tamrakar, Naresh Kazi (Bulletin of the Department of Geology, 2013)
Thick sedimentary sequence deposited in the foreland basin of the Nepal Himalaya is represented by the Siwalik Group. The Siwalik Group is well exposed in the Samari-Sukaura River area. The present study is focused in southern portion of the MBT around the Samari-Sukaura area for its depositional environment. The Middle Siwaliks of the Sukaura Road sections is overlained by the Lower Siwaliks which is separated by the Karki Khola Thrust. Extension of the Lower Siwaliks in the Jyamire Khola and the Bundal Khola becomes wider in the eastern Zone. Repetition of the Lower Siwaliks along the southern margin of the MBT is recognized. Depending on lithofacies assemblage and facies analysis, the two broad facies assemblages FA1 and FA2 have been distinguished. FA1 shows SB, FF, LA, LS and CH architectural elements and is interpreted as a product of the fine-grained meandering river system. FA2 shows SB, FF, LA, DA and CH architectural elements and is interpreted as a product of sandy mixed-load meandering river system. DOI: http://dx.doi.org/10.3126/bdg.v16i0.8884 Bulletin of the Department of Geology Vol. 16, 2013, pp. 53-64